Exonerating Children’s Pitfalls in Learning Language: Parents-Teachers Partnership During the Covid-19 Pandemic Restrictions (American Journal of Arts and Human Science, 2022)
Parental involvement in children’s learning is crucial in enhancing their performance in school. With the restrictions brought by the COVID-19 pandemic, their roles at home made a difference. This action research aimed to find out the importance of parents in helping children who have the difficulties in grasping their lesson in English. Moreover, this provided enough information which presented the panoramic perspectives and strategies employed by parents to exonerate these children from the shackle of ignorance. The participants of this study were parents who were considered as partners in teaching their children at home. Results showed that the challenges they experienced were children who were unresponsive and lacked focus. The strategies they employed in teaching struggling learners were the utilization of online resources, allotted reading time, they barred their children from using gadgets. Also, it was revealed that the strategy was effective in helping the children to read. Parents gave words of encouragement to their children that they needed to focus on their studies amidst the pandemic. Thus, it was looked forward that teachers in all level should also have to utilize the same strategy.